CUSTOMER FLOW TIME REDUCTION AT BARBERSHOP XYZ BARBERSHOP WITH SIX SIGMA ANALYSIS - Ethanael Alexander (Journal of Social and Economics Research, 2024)
This research analyzes the long customer flow times at Barbershop XYZ Harapan Indah during peak hours (11:00 AM-3:00 PM) on Saturdays. The current flow time of 76.69 minutes aims to be reduced to 60 minutes. Through direct observation and interviews, three root causes were identified: unseparated grooming and treatment spaces, lack of capster break schedules, and capsters' inability to recommend cutting styles. To address these issues, several solutions were proposed using the SCAMPER technique during the Improvement stage of DMAIC. Firstly, an AI kiosk will be introduced to provide haircut recommendations, aiding both customers and capsters. Secondly, weekly training sessions will be held to enhance capsters' skills. Lastly, a break schedule will be established for capsters to optimize working time. Lastly, the barbershop layout will be reorganized to separate grooming and treatment areas, allowing capsters to focus on grooming while helpers handle treatments. These improvements are expected to reduce the customer flow time from 76.69 minutes to 60 minutes, enhancing overall service efficiency at Barbershop XYZ Harapan Indah. Apart from that, this research also proposes several recommendations in terms of control plans to control the solutions that have been proposed so that improvements can be maintained.